Model of geometric deviations in milling with three error sources - Corrado, Andrea; Polini, Wilma (Manufacturing Technology Journal, 2021)
The milling process is widely used industrially and the quality of the obtained milled products should be controlled because it affects their performance in exercise. This work correlates the quality of the machined surfaces with the adopted locating system, the shape deviations of the workpiece datum and the machine tool. An analytical model was set up and implemented through Matlab® to simulate the quality effects of a milling process. It was applied to two face milling processes characterized by two different locator configurations. It was proved that machine tool volumetric error influences the flatness of the milled surface, while the locator configuration and the datum form deviation affect the orientation of the milled surface, as should be actually.
Keywords: Error model; Geometric source error; Milling accuracy; Locators